Testicular Nitric Oxide and Thiobarbituric Acid Reactive Substances Levels in Obstructive Azoospermia: A Possible Role in Pathophysiology of Infertility. (20th March 2006) - Başar Başar, M. Murad M. Murad; Kisa Kisa, Üçler Üçler; Tuğlu Tuğlu, Devrim Devrim; Yilmaz Yilmaz, Erdal Erdal; Başar Başar, Halil Halil; Çağlayan Çağlayan, Osman Osman; Batislam Batislam, Ertan Ertan
Abstract : Objective . The aim of the study is to evaluate the levels of nitrite/nitrate and thiobarbituric acid reactive substances (TBARS) and their relationship with seminal parameters in experimental obstructive azoospermic rats to explain the possible mechanism of impaired sperm quality in obstructive azoospermia. Methods . A total of 10 male Spraque-Dawley rats underwent bilateral vas resection and ligation (Group- 1 = vasectomy group ). The findings were compared with control group (Group- 2 = sham group, n = 10 ). Animals were sacrificed 8 weeks after surgery. Testes were removed and used for the evaluation of nitrate/nitrite and TBARS levels and for histology. Epididymal-aspirated seminal plasma was used for semen count and morphological analysis according to the Kruger criteria. Results . Testicular tissue nitrate/nitrite and TBARS levels were35.7 ± 3.1 μ mol/g protein and3.7 ± 0.1 nmol/g protein in Group-1, and19.3 ± 0.7 μ mol/g protein and3.1 ± 0.1 nmol/g protein in Group-2, respectively. Both parameters showed statistical differences between the two groups. Testicular tissue nitrate/nitrite and TBARS levels showed negative and statistically significant correlations with sperm motility and morphology. Conclusions . The present study showed that testicular nitrate/nitrite and TBARS levels were increased in obstructive azoospermia. For that reason, we concluded that antioxidant treatment can be recommended to patients before sperm extraction for artificial reproduction due to obstructive infertility after vasectomy reversal.